Dodajalna izdelava : Od hitre izdelave prototipov do 3D tiskane inovacije - Drstvenšek , Igor; Brajlih, Tomaž (University of Maribor Press, 2020)
Additive Manufacturing: From Rapid Prototyping to 3D Printed Innovation. The textbook describes additive manufacturing and its features as the youngest among production technologies. The basic principle of the operation of additive technologies and the scope of their application are explained. The technological peculiarities of each type of additive technologies and the design features for the additive manufacturing are explained. Rapid tooling is an area that has in the past served as an intermediate stage between rapid prototyping and pre-production runs of the final product. The textbook, however, presents the opportunities these technologies provide in tooling today. Successful use of additive manufacturing in the industry is essential for its economy, so the continuation of the textbook is dedicated to determining the productivity and accuracy of additive manufacturing. The chapter on economy of additive manufacturing introduces a new and patented method of computing equipment performance that takes into account both the design complexity of the product and the utilization of equipment.